Penyelenggaraan Kegiatan Lapak Baca Dinas Perpustakaan dan Kearsipan Kota Padang Panjang untuk Meningkatkan Minat Baca Anak Sekolah Dasar di Padang Panjang - Cahyani, Putty Amalia Regita; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
Abstract This paper discusses the implementation of reading stalls activities made by the library office and archives of the city of Padang Panjang as an effort to increase reading interest in elementary school children in Padang Panjang. The purpose of this paper is to: (1) describe how the implementation of reading stalls activities to increase reading interest in elementary school children in Padang Panjang; (2) describe the obstacles faced in the implementation of reading stalls activities; (3) describe the efforts that can be made to overcome the obstacles faced in the implementation of reading booth activities. The research method used in this writing is descriptive method. Data collection is done through interviews and through direct observation. The stages of organizing lapak activities are read as follows. First, planning, at this stage the regional library determines the schedule, and which schools will be visited. Second, the implementation of activities, procedures for implementing activities include: (1) the team first meets the school to coordinate whether this activity can be started; (2) one of the staff becomes the host to notify the procedure of the event and other staff to discipline students; (3) staff distribute books 1 book 1 child; (4) the team allows students to read approximately 15 minutes and presents challenges if there are students who dare to advance to retell what they read will be rewarded; (5) awarding. Constraints faced in carrying out reading stall activities are: (1) many reading materials that have been damaged such as torn; (2) lack of librarian staff to support the implementation of activities; (3) the existence of reading material that is not in accordance with the age of the student. Efforts can be made to overcome these obstacles: (1) libraries are expected to procure new collection purchases; (2) libraries should increase the number of librarians deployed to carry out reading booth activities, or libraries to open job openings; (3) before conducting the reading stall activities, the team re-checks the books to be taken.Keywords:Â actives, reading stalls, reading interest